Colchicine for stroke prevention in patients with coronary artery disease: a systematic review and meta‐analysis. (26th March 2020) - Katsanos, A. H.; Palaiodimou, L.; Price, C.; Giannopoulos, S.; Lemmens, R.; Kosmidou, M.; Georgakis, M. K.; Weimar, C.; Kelly, P. J.; Tsivgoulis, G.
Abstract : Background and purpose: Although clinical trials suggest that colchicine may reduce the risk of vascular events in patients with a history of coronary artery disease, its effect on the prevention of cerebrovascular events still remains unclear. Methods: A systematic review and meta‐analysis was performed of all available randomized controlled trials (RCTs) reporting on incident strokes during the follow‐up of patients with a history of cardiovascular disease randomized to colchicine treatment or control (placebo or usual care). Results: Four RCTs were identified, including a total of 5553 patients (mean age 61 years, 81% males), with a follow‐up ranging from 1 to 36 months. Colchicine treatment was associated with a significantly lower risk of incident stroke during follow‐up compared to control (risk ratio 0.31, 95% confidence interval 0.13–0.71), without heterogeneity across included studies ( I 2 = 0%). Based on the pooled incident stroke rate of control groups (0.9%) in the included RCTs, it was estimated that administration of low‐dose colchicine to 161 patients with coronary artery disease would prevent one stroke during a follow‐up of 23 months. Conclusion: Colchicine treatment decreases stroke risk in patients with a history of coronary artery disease. The effect of colchicine in secondary stroke prevention is currently being evaluated in an ongoing RCT.